1989
DOI: 10.1017/s0033291700005547
|View full text |Cite
|
Sign up to set email alerts
|

Louis-Victor Marcé, 1828–1864: anorexia nervosa's forgotten man

Abstract: SYNOPSISAn English translation of Marcé's original description of anorexia nervosa is reproduced with a brief comment on the author and his work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…In fact, several of the earliest medical descriptions of AN in the 19th century highlighted that the sufferers' reasons for self-starvation typically were inappetence, feelings of fullness and abdominal pain or constipation [2]. Likewise, contemporary descriptions of EDs from non-Western countries, e.g., Hong Kong, emphasise that gastrointestinal symptoms are a common justification for self-starvation in AN [3].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, several of the earliest medical descriptions of AN in the 19th century highlighted that the sufferers' reasons for self-starvation typically were inappetence, feelings of fullness and abdominal pain or constipation [2]. Likewise, contemporary descriptions of EDs from non-Western countries, e.g., Hong Kong, emphasise that gastrointestinal symptoms are a common justification for self-starvation in AN [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the DSM-V revised this ED type and called it "Other Specified Feeding or Eating Disorder" (OSFED). Moreover, the DSM-V introduced the definition of Avoidant/restrictive food intake disorder (ARFID) that was distinct from AN and BN in that there is no body image disturbance [2].The first description of AN in the 19th century revealed that the sufferers' reasons for self-starvation generally were strictly connected to inappetence, feelings of fullness and abdominal pain or constipation [12,13]. Since then, a wide range of GI symptoms in ED patients has been described [14].More recently, a prospective study reported that the majority of ED patients complained of postprandial fullness (96%) and abdominal distention (90%) [15], and pooled GI symptoms were significantly correlated with hypochondriasis, producing a deleterious influence of psychiatric comorbidities on GI discomfort [15].BED co-occurs with a variety of psychiatric disorders, especially mood (54.2%), anxiety (37.1%) and substance use disorders (24.8%) [16].…”
mentioning
confidence: 99%
“…Essas pacientes, quando orientadas a fazer uma dieta mais suficiente, opunham--se com infinitas estratégias e uma resistência indobrável. Para ele, "estas pacientes não são dispépsicas, mas insanas" (apud Silverman, 1989).…”
Section: Primeiras Descrições Da Anorexia Nervosaunclassified